The prevalence and intensity of ectoparasites that infects tilapia (Oreochromis niloticus) in floating net cages - Kavinta Melanie; Sayyid Afdhal El Rahimi; Amaliah Suryani; Siska Mellisa; Rianjuanda Djamani; Ratna Mutia Aprilla (Depik, 2022)
Ectoparasites which often attack tilapia include Trichodina sp., Dactylogyrus spp., Gyrodactylus spp., and Epistylis spp. This research aims to determine the types, prevalence, and intensity of ectoparasites found on tilapia (Oreochromis niloticus) in the floating net cages of Batanghari River, Jambi. The research was conducted from February through March 2020. A survey method is carried out through direct sampling at the study site to identify the tilapia ectoparasites. The sampling technique is done using random sampling. Ninety fish were taken for parasite inspection at the Fish Quarantine, Quality Control, and Safety of Fishery Products Class I Jambi Station. The observations found three types of ectoparasites namely Dactylogyrus sp., Epistylis sp., and Oodinium sp. The highest ectoparasite prevalence rate was found from the species Epistylis sp. with a value of 37.7% and an intensity value of 24.7 ind/fish. The prevalence of Dactylogyrus sp. was 26.6% and an intensity value of 1.3 ind/fish. The lowest prevalence value was from Oodinium sp. with a prevalence value of 7.7% and an intensity value of 3.2 ind/fish. The prevalence and intensity values of tilapia ectoparasites based on their locations were 56.6% and 23 ind/fish (station I), 50% and 18.6 ind/fish (station II) and 43.3% and 17.6 ind/fish (station III). The types of ectoparasites found on tilapia in this study were Epistylis sp., Oodinium sp., and Dactilogyrus sp. The parasite with the highest prevalence and intensity found during the survey was Epistylis sp.Keywords:EctoparasitesTilapiaPrevalenceIntensityFloating net cages